Competing mechanisms of plasticity impair compensatory responses to repetitive apnoea. (7th July 2019) - Fields, Daryl P.; Braegelmann, Kendra M.; Meza, Armand L.; Mickelson, Carly R.; Gumnit, Maia G.; Baker, Tracy L.
Abstract : Key points: Intermittent reductions in respiratory neural activity, a characteristic of many ventilatory disorders, leads to inadequate ventilation and arterial hypoxia. Both intermittent reductions in respiratory neural activity and intermittent hypoxia trigger compensatory enhancements in inspiratory output when experienced separately, forms of plasticity called inactivity‐induced inspiratory motor facilitation (iMF) and long‐term facilitation (LTF), respectively. Reductions in respiratory neural activity that lead to moderate, but not mild, arterial hypoxia occludes plasticity expression, indicating that concurrent induction of iMF and LTF impairs plasticity through cross‐talk inhibition of their respective signalling pathways. Moderate hypoxia undermines iMF by enhancing NR2B‐containing NMDA receptor signalling, which can be rescued by exogenous retinoic acid, a molecule necessary for iMF. These data suggest that in ventilatory disorders characterized by reduced inspiratory motor output, such as sleep apnoea, endogenous mechanisms of compensatory plasticity may be impaired, and that exogenously activating respiratory plasticity may be a novel strategy to improve breathing. Abstract: Many forms of sleep apnoea are characterized by recurrent reductions in respiratory neural activity, which leads to inadequate ventilation and arterial hypoxia. Both recurrent reductions in respiratory neural activity and hypoxia activate mechanisms of compensatory plasticity that augment inspiratory output and lower the threshold for apnoea, inactivity‐induced inspiratory motor facilitation (iMF) and long‐term facilitation (LTF), respectively. However, despite frequent concurrence of reduced respiratory neural activity and hypoxia, mechanisms that induce and regulate iMF and LTF have only been studied separately. Here, we demonstrate that recurrent reductions in respiratory neural activity ('neural apnoea') accompanied by cessations in ventilation that result in moderate (but not mild) hypoxaemia do not elicit increased inspiratory output, suggesting that concurrent induction of iMF and LTF occludes plasticity. A key role for NMDA receptor activation in impairing plasticity following concurrent neural apnoea and hypoxia is indicated since recurrent hypoxic neural apnoeas triggered increased phrenic inspiratory output in rats in which spinal NR2B‐containing NMDA receptors were inhibited. Spinal application of retinoic acid, a key molecule necessary for iMF, bypasses NMDA receptor‐mediated constraints, thereby rescuing plasticity following hypoxic neural apnoeas. These studies raise the intriguing possibility that endogenous mechanisms of compensatory plasticity may be impaired in some individuals with sleep apnoea, and that exogenously activating pathways giving rise to respiratory plasticity may be a novel pharmacological strategy to improve breathing. Key points: Intermittent reductions in respiratory neural activity, a characteristic of many ventilatory disorders, leads to inadequate ventilation and arterial hypoxia. Both intermittent reductions in respiratory neural activity and intermittent hypoxia trigger compensatory enhancements in inspiratory output when experienced separately, forms of plasticity called inactivity‐induced inspiratory motor facilitation (iMF) and long‐term facilitation (LTF), respectively. Reductions in respiratory neural activity that lead to moderate, but not mild, arterial hypoxia occludes plasticity expression, indicating that concurrent induction of iMF and LTF impairs plasticity through cross‐talk inhibition of their respective signalling pathways. Moderate hypoxia undermines iMF by enhancing NR2B‐containing NMDA receptor signalling, which can be rescued by exogenous retinoic acid, a molecule necessary for iMF. These data suggest that in ventilatory disorders characterized by reduced inspiratory motor output, such as sleep apnoea, endogenous mechanisms of compensatory plasticity may be impaired, and that exogenously activating respiratory plasticity may be a novel strategy to improve breathing.